STUDY OF SURFACE FINISH OF STEREOLITHOGRAPHY (SLA™) PRODUCTS - Ismet Hari Mulyadi (Jurnal Teknik Mesin, 2004)
Recently, development of Rapid Prototyping technique refers to Rapid Tooling (RT) application. Unfortunately, considering the limitation of technology available and suitable material, the research activities are respectively stagnating on improvement the method using building tool with recent technology and material. However, the problem being faced by researchers are not only limitation pre-mentioned above but also due to difficulties to gain tool with high part qualities. Therefore, in this present research, the part qualities especially surface finish would become primary consideration. Moreover, the obstacles in gaining the part with high surface finish on RP technology is the staircase effect, which is influenced by orientation angle. So, to reach the aim of research in observing the orientation angle for which part would have good surface finish, the orientation angle will be varied. The result shows that surface roughness of SLA built on 0 and 11,25 considerably have good impact on surface finish of the part building directly from Rapid Prototyping machine.